Alpha-Fe2O3 / SnO2 nanoneedle heterojunction gas sensitive material as well as preparation method and application thereof
By preparing α-Fe2O3/SnO2 nanoneedle heterogas-sensitive material, the existing α-Fe2O3 gas-sensitive material has solved the problems of high working temperature, poor selectivity and long response time, and high sensitivity detection and low working temperature for nitrogen dioxide are achieved.
Patent Information
- Application Number
- CN202510000861.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-08
AI Technical Summary
When existing α-Fe2O3 gas-sensitive materials are used to detect nitrogen dioxide, the operating temperature is high, the selectivity is poor, and the response and recovery time is long.
The α-Fe2O3/SnO2 nanoneedle heterogas-sensitive material was used to prepare an α-Fe2O3/SnO2 nanoneedle composite material by hydrothermal reaction of ceramic tubes loaded with α-Fe2O3 nanoneedle with a mixed solution of tin chloride and urea.
The working temperature of the gas-sensitive material is significantly reduced, the response value to nitrogen dioxide is increased, and the gas-sensitive performance of the material is enhanced.
Smart Images

Figure CN119774666A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation and application of inorganic composite materials, and specifically relates to an alpha-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material and a preparation method and application thereof. Background Art Nitrogen dioxide (NO2), with the chemical formula NO2 and a molecular weight of 46.006, is a reddish-brown gas with a pungent odor. In the fields of materials science and environmental science, NO2 has attracted much attention due to its potential harm to human health and the environment. NO2 mainly comes from industrial emissions, especially the combustion of fossil fuels. It not only poses a direct threat to human health, but also indirectly affects air quality and human health by reacting with other atmospheric components to produce particulate matter and ozone. The concentration of NO2 is one of the key indicators for assessing the degree of air pollution, and it is also an important precursor of tropospheric ozone and photochemical smog.
[0002] The NO2 molecule structure contains a large π bond, which exhibits paramagnetism, an ONO bond angle of about 134.3°, and a NO bond length of 119.7 picometers. This structure makes NO2 highly reactive, easily polymerized to form nitrogen tetroxide (N2O4), and participates in a variety of chemical reactions as an oxidant under specific conditions. These characteristics of NO2 make it play an important role in material synthesis and industrial processes, while also increasing the complexity of its environmental monitoring and control. According to the Health and Safety Code, the concentration of NO2 that humans are exposed to should not exceed 3 ppm, and the exposure time should not exceed 8 hours to reduce health risks. Therefore, the development of highly sensitive and selective NO2 detection technology is essential to protect the environment and human health. .
[0003] Gas sensors are devices that detect gas based on gas-sensitive properties, and there are many types of them. Among them, semiconductor gas sensors are widely used due to their practicality and a wide variety of sensitive materials. According to the working principle, semiconductor gas sensors can be divided into two types: resistive and non-resistive. Resistive sensors are highly praised for their simple working principle, low cost and excellent stability. As an n-type semiconductor, α-Fe2O3 has the advantages of wide band gap, high thermal stability and easy synthesis, and is widely used in the field of gas sensors. However, there are also some defects, such as high operating temperature, poor gas selectivity, and long response and recovery time.
[0004] In the field of materials science, the development of gas sensing technology is gradually shifting from single metal oxide sensors to composite metal oxide sensors. Single metal oxides have limited room for improvement in gas sensing performance due to their inherent physical and chemical properties. In contrast, composite metal oxides show greater research potential due to their flexible chemical components and the special synergistic effect of heterojunctions. Based on the construction of heterostructures, changes in the material band structure can be triggered, while providing more active sites, thereby significantly improving the catalytic activity of the material. This change has a positive effect on enhancing the gas-sensing performance of sensitive materials.
[0005] Patent CN118883651A discloses a method for detecting heptanoic acid and heptaldehyde gas using a double-layer structure of tin oxide and iron oxide gas-sensitive material: the gas sensor based on the double-layer structure of tin oxide and iron oxide is a double-layer structure composed of a tin oxide layer and an iron oxide layer, the tin oxide layer is used as a gas-sensitive layer, the iron oxide layer is used as a catalytic layer, the iron oxide layer is composed of iron oxide particles with a diameter of 100-200 nm, and the tin oxide layer is composed of tin oxide nanosheets with a thickness of 6-8 nm, a length of 10-30 nm, and a width of 5-20 nm. The gas sensor achieves a specific response to heptaldehyde and heptanoic acid by covering the catalytic layer on the gas-sensitive layer. At a specific temperature, only heptaldehyde and heptanoic acid can pass through the catalytic layer to reach the gas-sensitive layer, thereby achieving a highly selective and highly stable specific response to heptaldehyde and heptanoic acid. The gas sensor has a specific response only to heptanoic acid and heptanal. At a temperature of 300 °C, its gas response values to 10 ppm concentration gas reach 2.97 and 2.86 respectively, while it has no response to the other 30 VOC gases and inorganic gases.
[0006] However, there is no report on the specific detection of nitrogen dioxide by α-Fe2O3 / SnO2 materials in the prior art, and the working temperature of the existing α-Fe2O3 gas-sensitive materials for detecting nitrogen dioxide is relatively high, which limits its application. Summary of the invention
[0007] In view of the problems in the prior art that α-Fe2O3 as a gas-sensitive material has high operating temperature, poor gas selectivity, and long response and recovery time, the present invention provides an α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material and a preparation method and application thereof, which can effectively improve the gas-sensing performance of α-Fe2O3 and exhibit an extremely high response value to NO2 while lowering the operating temperature.
[0008] The present invention is achieved through the following technical solutions: A method for preparing an α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material comprises the following steps: (1) Preparation of ceramic tubes loaded with α-Fe2O3 nanoneedles: Add a mixed solution of ferric chloride and sodium sulfate and a ceramic tube into a reactor, and perform a hydrothermal reaction at 120-160 °C for 10-14 h. After the reaction is completed, take out the ceramic tube, dry it, and anneal it to obtain a ceramic tube loaded with α-Fe2O3 nanoneedles; (2) Preparation of α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material: Dissolve tin chloride and urea in water to obtain a mixed solution, and add the ceramic tube loaded with α-Fe2O3 nanoneedles in step (1) into a reactor for hydrothermal reaction at 80-100°C for 1-6 hours. After the reaction is completed, take out the ceramic tube, dry it, and anneal it to obtain an α-Fe2O3 / SnO2 nanoneedle composite gas-sensitive material.
[0009] Furthermore, the ferric chloride in step (1) is FeCl3.6H2O, the concentration of the ferric chloride solution is 0.01-0.03 g / mL, and the concentration of sodium sulfate is 0.005-0.008 g / mL; the tin chloride in step (2) is SnCl2·2H2O, the concentration of tin chloride in the mixed solution is 0.01-0.03 g / mL, and the concentration of urea is 0.002-0.005 g / mL.
[0010] Furthermore, the ceramic tube in step (1) is an alumina ceramic tube.
[0011] Furthermore, the annealing conditions in step (1) and step (2) are: 450-550°C for 1-3 hours, and a heating rate of 1-3°C / min.
[0012] Furthermore, in step (1), the hydrothermal reaction is carried out at 140°C for 12 h. The α-Fe2O3 nanoneedles grown at this temperature and reaction time are large in size, uniform in distribution, compact in growth, and have good crystallinity.
[0013] Furthermore, in step (2), the hydrothermal reaction is carried out at 95 °C for 4 h. In the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material grown at this temperature and reaction time, SnO2 is uniformly distributed on the α-Fe2O3 nanoneedles in the form of nanoparticles, and the size and number of SnO2 particles increase with the increase of hydrothermal time.
[0014] In the present invention, the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material is prepared by the preparation method.
[0015] In the present invention, the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material is used in detecting NO2.
[0016] Beneficial Effects (1) The present invention grows α-Fe2O3 nanoneedles upright on the surface of an alumina ceramic tube, and then calcines them in a tube furnace to prepare a pure phase α-Fe2O3 material. The preparation method is simple and can obtain a nanoneedle structure with uniform morphology and size; (2) The present invention adopts a secondary hydrothermal method to synthesize α-Fe2O3 / SnO2 nanoneedle material and prepare α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material. The prepared α-Fe2O3 and SnO2 are evenly distributed. The structure of the prepared α-Fe2O3 / SnO2 is conducive to the advantages of nn heterojunction such as band bending, electron transfer, multiple active sites, and increased surface area, and has a lower operating temperature; (3) The preparation method of the present invention is simple, the product has high crystallinity and good stability, and is suitable for preparing highly economical gas sensor materials. In addition, the sensor prepared by α-Fe2O3 / SnO2 nanoneedle heterojunction gas sensitive material can effectively improve the gas sensing performance of α-Fe2O3, and exhibits an extremely high response value to NO2 while lowering the operating temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a scanning electron microscope (SEM) image of the ceramic tube loaded with α-Fe2O3 nanoneedles prepared in Example 1; Figure 2 is the X-ray diffraction (XRD) pattern of the ceramic tube loaded with α-Fe2O3 nanoneedles prepared in Example 1; Figure 3 This is a scanning electron microscope (SEM) image of the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material prepared in Example 1-4; Figure 4 The transmission microscopy (TEM) images of the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive materials prepared under different conditions in Example 1; Figure 5 is the X-ray diffraction (XRD) pattern of the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material prepared in Example 1; Figure 6 is an X-ray photoelectron spectroscopy (XPS) spectrum of the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material prepared in Example 1; Figure 7 It is the response value curve of different gas-sensitive materials at different temperatures; Figure 8 This is a diagram showing the selectivity of different gas-sensitive materials for different gases; Fig. 9 The graph shows the cyclic stability of different gas-sensitive materials to 50 ppm NO2 gas; Fig.10This is the response curve of different gas-sensitive materials to different concentrations of nitrogen dioxide. DETAILED DESCRIPTION
[0018] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.
[0019] Example 1 (1) The alumina ceramic tube was placed in deionized water and ethanol and cleaned with an ultrasonic instrument for 5 minutes, then dried for later use; (2) Place the cleaned alumina ceramic tube into the inner lining of a polytetrafluoroethylene reactor, slowly drip α-Fe2O3 growth solution (add 40 ml of deionized water to 0.5517 g FeCl3.6H2O and 0.2870 g NaSO4, and stir on a magnetic stirrer for 30 min to dissolve), seal it, place it in a forced air drying oven, and perform hydrothermal reaction at 140 °C for 12 h. Take out the ceramic tube, clean and dry it, and place it in a tubular furnace at a heating rate of 3 °C / min and keep it at 500 °C for 2 h to obtain a ceramic tube loaded with α-Fe2O3 nanoneedles. Its scanning electron microscope (SEM) image is shown in the figure below. Figure 1 As shown, from Figure 1 It can be seen that the α-Fe2O3 nanoneedle structure is in-situ grown on the ceramic tube, and the α-Fe2O3 nanoneedle grows densely and uniformly; the XRD spectrum of the ceramic tube loaded with α-Fe2O3 nanoneedles is shown in Figure 2 As shown, from Figure 2 It can be seen that the α-Fe2O3 nanoneedles have good crystallinity and no other impurity peaks appear; (3) The ceramic tube loaded with α-Fe2O3 nanoneedles in step (1) was placed in the inner lining of the reactor, and a mixed solution of SnCl2·2H2O and CH4N2O was added (0.4605 g SnCl2·2H2O and 0.1213 g CH4N2O were added to 20 ml deionized water respectively, stirred for 20 min, and then mixed and stirred for 20 min). After sealing, the tube was placed in a forced air drying oven for hydrothermal treatment at 95 °C for 4 h. After the hydrothermal treatment was completed, the ceramic tube was removed from the cooled reactor, cleaned, and placed in a drying oven for constant temperature drying at 60 °C for 10 h. The tube was placed in a tubular furnace and heated at a rate of 3 °C / min and kept at 500 °C for 2 h to obtain α-Fe2O3 / SnO2 (SEM) as shown in the figure below. Figure 3 (c) and transmission electron microscopy (TEM) images Figure 4 As shown in the figure, it can be seen that SnO2 nanoparticles grow on the surface of the ceramic tube loaded with α-Fe2O3. The X-ray diffraction (XRD) pattern of the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material is shown in the figure. Figure 5 As shown in the figure, it can be observed that the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material has an obvious α-Fe2O3 characteristic peak, but the SnO2 characteristic peak is not obvious; for this reason, the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material was tested by X-ray photoelectron spectroscopy (XPS), and the spectrum is shown in Figure 6 As shown, the 3d orbital spectrum of Sn can be clearly observed, indicating the successful synthesis of α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive materials.
[0020] Embodiment 2-4 In Examples 2 to 4, the reaction time in step (3) of Example 1 was changed, and the remaining steps were the same as in Example 1. The reaction temperature and reaction time in step (3) of Examples 2 to 4 are shown in Table 1 below: Table 1 Reaction temperature and reaction time table of step (3) of Examples 2 to 4 The scanning electron microscope (SEM) image of the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material prepared in Example 2 is as follows: Figure 3 As shown in (a), SnO2 cannot be clearly observed on the surface of the α-Fe2O3 nanoneedle; the scanning electron microscope (SEM) image of the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material prepared in Example 3 is as follows Figure 3 As shown in (b), at this temperature and reaction time, the surface of the α-Fe2O3 nanoneedle has a granular feel; the scanning electron microscopy (SEM) results of the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material prepared in Example 4 are as follows Figure 3 As shown in (d), SnO2 is distributed in large quantities on the surface of α-Fe2O3 nanoneedles, SnO2 particles appear to aggregate, some appear to be thin rods, and the thickness of the nanoneedles increases.
[0021] Application test of gas-sensitive materials (α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive materials) The ceramic tube (α-Fe2O3) loaded with α-Fe2O3 nanoneedles prepared in step (2) of Example 1, the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material (α-Fe2O3 / SnO2 (4 h)) prepared in step (3) of Example 1, the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material prepared in Example 2 (α-Fe2O3 / SnO2 (1 h)), the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material prepared in Example 3 (α-Fe2O3 / SnO2 (2 h)), and the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material prepared in Example 4 (α-Fe2O3 / SnO2 (6 h)) were welded to a base to prepare corresponding gas sensors, and the operating temperature, response value and selectivity of different materials were detected and analyzed.
[0022] 1) Test the response values of four α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive materials (α-Fe2O3, α-Fe2O3 / SnO2 (1 h), α-Fe2O3 / SnO2 (2 h), α-Fe2O3 / SnO2 (4 h), α-Fe2O3 / SnO2 (6 h)) to NO2 at different temperatures. The concentration of NO2 gas used for the test was 50 ppm. The test results are as follows Figure 7 shown by Figure 7 It can be seen that the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material (α-Fe2O3 / SnO2 (4 h)) has the best gas-sensitive performance at 220 ℃, which is significantly stronger than the other three gas-sensitive materials, and the operating temperature is greatly reduced.
[0023] 2) The response values of the ceramic tube (α-Fe2O3) loaded with α-Fe2O3 nanoneedles and four α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive materials (α-Fe2O3 / SnO2 (1 h), α-Fe2O3 / SnO2 (2 h), α-Fe2O3 / SnO2 (4 h), α-Fe2O3 / SnO2 (6 h)) in different gas atmospheres (formaldehyde, ammonia, methanol, ethanol, isopropanol, triethylamine, nitrogen dioxide) were tested. The gas concentration was 50 ppm and the temperature was 220 °C. The test results are shown in the figure. Figure 8 shown by Figure 8 It can be seen that the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material (α-Fe2O3 / SnO2 (4 h)) prepared in Example 1 has extremely high selectivity for NO2.
[0024] 3) The cyclic stability of the ceramic tube loaded with α-Fe2O3 nanoneedles (α-Fe2O3) and four α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive materials (α-Fe2O3 / SnO2 (1 h), α-Fe2O3 / SnO2 (2 h), α-Fe2O3 / SnO2 (4 h), α-Fe2O3 / SnO2 (6 h)) to 50 ppm NO2 at 220 °C and within six cycles was tested. The test results are shown in Figure 3. Fig. 9 As shown, it was found that the above materials all have good cycle stability.
[0025] 4) The response values of the ceramic tube (α-Fe2O3) loaded with α-Fe2O3 nanoneedles and four α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive materials (α-Fe2O3 / SnO2 (1 h), α-Fe2O3 / SnO2 (2 h), α-Fe2O3 / SnO2 (4 h), α-Fe2O3 / SnO2 (6 h)) to different concentrations of NO2 were tested. The detection temperature was set to 220 °C. The test results are shown in the figure. Fig.10 As shown, it was found that with the increase of NO2 concentration, the gas response value of the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material (α-Fe2O3 / SnO2 (4 h)) prepared in Example 1 continued to increase, and it still had a high gas response value at low concentrations.
Claims
1. A method for preparing α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material, characterized in that: The following steps are involved: (1) Preparation of ceramic tubes loaded with α-Fe2O3 nanoneedles: Add a mixed solution of ferric chloride and sodium sulfate and a ceramic tube into a reactor, and perform a hydrothermal reaction at 120-160 °C for 10-14 h. After the reaction is completed, take out the ceramic tube, dry it, and anneal it to obtain a ceramic tube loaded with α-Fe2O3 nanoneedles; (2) Preparation of α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material: Dissolve tin chloride and urea in water to obtain a mixed solution, and add the ceramic tube loaded with α-Fe2O3 nanoneedles in step (1) into a reactor for hydrothermal reaction at 80-100°C for 1-6 h. After the reaction is completed, take out the ceramic tube, dry it, and anneal it to obtain an α-Fe2O3 / SnO2 nanoneedle composite gas-sensitive material.
2. The method for preparing the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material according to claim 1, characterized in that: The ferric chloride in step (1) is FeCl3.6H2O, the concentration of the ferric chloride solution is 0.01-0.03 g / mL, and the concentration of sodium sulfate is 0.005-0.008 g / mL; the tin chloride in step (2) is SnCl2·2H2O, the concentration of tin chloride in the mixed solution is 0.01-0.03 g / mL, and the concentration of urea is 0.002-0.005 g / mL.
3. The method for preparing the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material according to claim 1, characterized in that: The ceramic tube in step (1) is an alumina ceramic tube.
4. The method for preparing the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material according to claim 1, characterized in that: The annealing conditions in step (1) and step (2) are: 450-550°C for 1-3 hours, and a heating rate of 1-3°C / min.
5. The method for preparing the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material according to claim 1, characterized in that: In step (1), the hydrothermal reaction is carried out at 140 °C for 12 h. The α-Fe2O3 nanoneedles grown at this temperature and reaction time are large in size, evenly distributed, densely grown, and have good crystallinity.
6. The method for preparing the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material according to claim 1, characterized in that: In step (2), the hydrothermal reaction was carried out at 95 °C for 4 h. Under this temperature and reaction time, the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material was grown, and SnO2 was uniformly distributed on the α-Fe2O3 nanoneedles in the form of nanoparticles. As the hydrothermal time increased, the size and number of SnO2 particles increased.
7. An α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the α-Fe2O3 / SnO2 nanoneedle heterojunction gas-sensitive material according to claim 7 in detecting NO2.
Citation Information
Cited By
Sn-MOF (at) SnO2 / Fe2O3 multilevel structure nano composite material, preparation method thereof and n-butyl alcohol gas sensor
CN121779776A